GpsB Coordinates StkP Signaling as a PASTA Kinase Adaptor in Streptococcus pneumoniae Cell Division - Stauberová, Václava; Kubeša, Bohumil; Joseph, Merrin; Benedet, Mattia; Furlan, Berenice; Buriánková, Karolína; Ulrych, Aleš; Kupčík, Rudolf; Vomastek, Tomáš; Massidda, Orietta; Tsui, Ho-Ching T; Winkler, Malcolm E; et al. (Journal of molecular biology, 2024)
StkP, the Ser/Thr protein kinase of the major human pathogen Streptococcus pneumoniae, monitors cell wall signals and regulates growth and division in response. In vivo, StkP interacts with GpsB, a cell division protein required for septal ring formation and closure, that affects StkP-dependent phosphorylation. Here, we report that although StkP has basal intrinsic kinase activity, GpsB promotes efficient autophosphorylation of StkP and phosphorylation of StkP substrates. Phosphoproteomic analyzes showed that GpsB is phosphorylated at several Ser and Thr residues. We confirmed that StkP directly phosphorylates GpsB in vitro and in vivo, with T79 and T83 being the major phosphorylation sites. In vitro, phosphoablative GpsB substitutions had a lower potential to stimulate StkP activity, whereas phosphomimetic substitutions were functional in terms of StkP activation. In vivo, substitutions of GpsB phosphoacceptor residues, either phosphoablative or mimetic, had a negative effect on GpsB function, resulting in reduced StkP-dependent phosphorylation and impaired cell division. The bacterial two-hybrid assay and co-immunoprecipitation of GpsB from cells with differentially active StkP indicated that increased phosphorylation of GpsB resulted in a more efficient interaction of GpsB with StkP. Our data suggest that GpsB acts as an adaptor that directly promotes StkP activity by mediating interactions within the StkP signaling hub, ensuring StkP recruitment into the complex and substrate specificity. We present a model that interaction of StkP with GpsB and its phosphorylation and dephosphorylation dynamically modulate kinase activity during exponential growth and under cell wall stress of S. pneumoniae, ensuring the proper functioning of the StkP signaling pathway.
Keywords: bakteriální proteiny; Protein Binding; buněčné dělení; vazba proteinů; Bacterial Proteins; Ser/Thr protein kinase; protein-protein interaction; cell division; Streptococcus pneumoniae; fosforylace; Cell Division; Protein Serine-Threonine Kinases; cell signalling; phosphorylation; protein-serin-threoninkinasy; signální transdukce; Phosphorylation; Signal Transduction